Community Video Profiling using Generative AI: A Scenario-Based Practical Experience to Catholic Community in Serpong Utara - I Made Murwantara; Hendra Tjahyadi; Pujianto Yugopuspito; Andriyani (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The aim of this community service is to have a scenario-based practical use of Artificial Intelligence to enhance video profiling which ultimately to increase people engagement to their religious life. Method: The activity making use of a practical approach to design and develop a profiling video via short training and demonstration to encourage religious activity in providing tutorial own video using available AI tools. It uses children scenario to develop the narration. Practical Applications: Participants using the Generative AI tools to help them in enhancing the existing scenario into video narration. The time efficient video preparation with benefit and less experience is achieved by configuring the setting of the tool and engaging to the scenario. Conclusion: Generative AI has potential to enhance video generation for religious stewardship by providing reliable, less time and more creative in providing a way to achieve goals. In adopting AI tools to support video creation generation with scenario-based has convey into its portion to religious community.